A New Classification Tool and a Systematic Review of Macroalgal Studies Disentangle the Complex Interactive Effects of Warming and Nutrient Enrichment on Primary Production - Endo, Hikaru; Gao, Xu (Frontiers in Marine Science, 2022)
Significant interactions between temperature and nutrient availability on primary production detected in some studies suggest that the effect of global warming can be synergized or antagonized by local nutrient environments. However, how these factors interact with each other has not yet been synthesized. In this paper, we reviewed the studies that examined the combined effects of these factors on the growth in marine macroalgae, which have been well studied compared to terrestrial plants and seagrasses. The significant interactions detected in many studies were mainly classified into four types. Synthesizing these types suggests that the positive effects of nutrient enrichment are synergized by elevated temperatures until optimal growth is reached, but are antagonized and turn into negative with further temperature elevation. Moreover, the negative effects of elevated temperature around optimal growth turn into positive with nutrient enrichment, but negative effects if further temperature elevation are synergized by nutrient enrichment. Although the negative effects of elevated temperature on macroalgal growth have been hypothesized to be antagonized by nutrient enrichment, this can only occur around optimal growth and the negative effects are synergized by nutrient enrichment in most cases. This knowledge provides new insights for macroalgal production and how to conserve primary producers under climate change.